Global stability of a commensal- host ecological model with limited resources and both are harvesting at a constant rate - Kumar, N Phani (Journal of Experimental Sciences, 2012)
In this paper we establish the global stability of a commensalism-host ecological model surviving with limited resources and both are harvesting at a constant rate, by constructing a suitable Liapunov’s function in case of co-existent equilibrium state.